Identifying and overcoming barriers to deployment of information technology projects in hotels. Issue 5 (14th August 2017) - Okumus, Fevzi; Bilgihan, Anil; Ozturk, Ahmet Bulent; Zhao, Xinyuan (Roy)
Abstract : Purpose: The purpose of this paper is to investigate potential barriers to deployment of information technology (IT) projects and evaluate strategies to overcome them in hotel companies. Design/methodology/approach: Empirical data were collected through a series of in-depth semi-structured interviews from IT managers, chief information officers, and hotel general managers. Findings: The research findings demonstrate that barriers to IT implementation occur in three different stages. They are pre-implementation (cost and return on investment, resistance by owners/executives); during the implementation (integration, time delays, vendor communication problems, and resistance by employees); and post-implementation (inadequate training and resistance from customers). Research limitations/implications: The research findings suggest a contingency approach where organizations should employ various specific strategies depending on the situation to overcome these barriers. Multiple theoretical perspectives should be utilized to evaluate potential barriers to IT projects and utilize specific strategies to overcome them. Originality/value: This is one of the first empirical studies which provide specific theoretical and practical implications on barriers when implementing IT projects in hotels.